Karakteristik sirup glukosa berbahan dasar umbut kelapa sawit dengan variasi konsentrasi enzim α-amilase dan suhu gelatinisasi - Maisaroh Maisaroh; Erista Adi Setya; Ngatirah Ngatirah (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2023)
Oil palm plants must be replanted every 25-30 years, resulting in waste of oil palm stems which can be taken for the stems. Palm sheaths have not been widely used even though they contain starch which is quite high at around 4.7%. Given the high starch of palm sheath, it can be used as a raw material for making glucose syrup. The aim of this research was to study the effect of α-amylase concentrations and gelatinization temperature on the characteristics of glucose syrup made from sheath palm oil. The randomized complete block design used as experimental design with two factors. The first factors were gelatinization temperature, consist of 3 levels (80°C, 90°C, and 100°C), The second factors were α-amylase concentration, consist of 3 levels (0,3%, 0,6%, and 1% w/w). The experiment using two replications. The analysis carried out were reducing sugar, total sugar, total solids, viscosity and organoleptic preferences (color, aroma, taste). The results of this study indicate that variations in gelatinization temperature have no significant effect on reducing sugar, total sugar, viscosity, total solids, organoleptic preferences (color, aroma and taste). The α-amylase concentration has a significant effect on reducing sugar, total sugar, viscosity and color, but had no significant effect on total solids, organoleptic preferences (aroma and taste). Based on the overall organoleptic preference, the best treatment is glucose syrup with a gelatinization temperature at 100°C and 1% w/w α-amylase concentration.